Contributions of Sustainable Biomass and Bioenergy in Agriculture Transitions Towards a Circular Economy - Tavira, Oloiva (2022)
The production of bioenergy and biofertilizers based on animal and plant biomass is a crucial pillar in circular economy (CE). CE conceptual model and main aims are closely related to the 3 “R” (reduce, reuse, and recycle) rule, which is to improve the use of resources, minimize waste, and assure sustain-ability. Although bioenergy offers many opportunities and could be an alternative to fossil fuels use, the path for a broader implementation of this type of activity is still long. This study marks the starting point or direction of research to be taken, ensuring the existence of benefits from plant and animal biomass for the production of bioenergy and biofertilizer, as well as the contributions of this type of production to the circular economy and the mitigation of the climate change impacts.